Classical and γδ T cells are each independently sufficient to establish protection against a classical strain of Klebsiella pneumoniae - Mackel, Joseph J.; Morffy Smith, Catherine; Wasbotten, Rachel K.; Twentyman, Joy; Rosen, David A. (Frontiers in Cellular and Infection Microbiology, 2022)
Infections with classical strains of the Gram-negative bacterium Klebsiella pneumoniae pose a significant clinical challenge due to rising antibiotic resistance. We previously established a lung inoculation plus challenge model using live, classical K. pneumoniae in order to study host protection. Here, we employ this model to dissect adaptive immune responses to this critical pathogen. First, we performed convalescent serum transfers from inoculated mice to naïve recipients and found that classical K. pneumoniae infection outcomes, unlike hypervirulent K. pneumoniae infection outcomes, were not improved. This suggests that circulating antibody responses alone are not sufficient to mediate protection against this classical strain. Hence, we evaluated the role of T cells in protection against classical K. pneumoniae reinfection and demonstrated that mice lacking T cells are unable to establish a protective response. However, mice individually deficient in either of the major T cell subsets, γδ or αβ (classical T cells), effectively mount a protective response, indicating either subset alone is sufficient to mediate protection. Sequestration of T cells in secondary lymphoid organs during the challenge infection did not ablate protection, indicating the circulating T cell pool is not required for the protective phenotype. Finally, we demonstrate that depletion of T cells during initial infection eliminates protection against challenge. Collectively, these experiments demonstrate the imperative contribution of T cells to protective immunity against classical K. pneumoniae and will guide further inquiries into host effector responses required to control this infection.